Academic Writing Challenges: Thesis Proposal Struggles Among 5th Semester PAI Students - Amirudin, Ivan Luthfi; Munawaroh, Anjar; Lazuardi, Thufail Labieb (Edudeena : Journal of Islamic Religious Education, 2024)
This research aims to analyze the challenges experienced by students of the Islamic Religious Education Study Program (PAI) of the State Islamic Religious Institute (IAIN) Kediri related to the policy of implementing the Higher Education curriculum where students write a thesis proposal in the fifth semester. The research approach uses qualitative case studies by collecting data through observation, interviews with students and lecturers, and documentation. Data triangulation is used to check the validity of the data. The data analysis technique uses interactive analysis which includes data reduction, data presentation, and drawing conclusions. The research results show that the challenges students face when writing proposals in the fifth semester are (1) difficulties in creating research concepts and understanding the content of the literature; (2) limitations in accessing references; (3) lack of understanding of the proposal structure; (3) less consistent writing of quotations; (4) difficulty in paraphrasing sentences, and (5) lack of understanding of directions from the supervisor. The five challenges above become increasingly difficult when students have poor technological mastery, disorganized time management and unstable psychological conditions. Some of the solutions offered include (1) strengthening research methodology course material; (2) additional training in writing scientific papers and using technology; (3) expanding the network of connections between students, both locally and between universities, to (4) increasing literacy to the maximum.